2021
DOI: 10.22456/1679-9216.118579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trochlear Dysplasia in Dogs with Medial Patellar Luxation - Comparative Studies

Abstract: Background: Medial patellar luxation (MPL) is one of the commonest orthopaedic diseases in small dog breeds. Although the bone deformities associated with canine medial patellar luxation are described in numerous studies, the pathogenesis of the condition is still disputable. What is more, there is no categorical evidence that luxation of the patella is associated to a shallow trochlear groove as no objective method for determination of trochlear depth and shape has been proposed. The aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…We accept our first hypothesis, as in this study the overall FTGA in dogs without MPL was smaller compared to MPL dogs, similarly to what other authors have recently reported. 8,14,15 Among SB and MLB populations, we discovered a mean FTGA of 128 ± 4.7 in SB and 119 ± 5.6 in MLB with cutoff values of 134 and 128 respectively. These data slightly differ from human literature, which suggests that a normal trochlea has an average sulcus angle of 138 ± 6 , while dysplastic trochleae have a sulcus angle >145 .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…We accept our first hypothesis, as in this study the overall FTGA in dogs without MPL was smaller compared to MPL dogs, similarly to what other authors have recently reported. 8,14,15 Among SB and MLB populations, we discovered a mean FTGA of 128 ± 4.7 in SB and 119 ± 5.6 in MLB with cutoff values of 134 and 128 respectively. These data slightly differ from human literature, which suggests that a normal trochlea has an average sulcus angle of 138 ± 6 , while dysplastic trochleae have a sulcus angle >145 .…”
Section: Discussionmentioning
confidence: 85%
“…[4][5][6] In people, the sulcus angle is usually assessed via radiographic skyline projection. 4,16,30 In veterinary medicine, this projection has been described to evaluate the FTGD, 8,31 but it is not routinely used. In this study, we opted for CT rather than radiographs, since a CT standardized methodology to accurately perform measurements on the femoral trochlear groove has been established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations